Long Noncoding RNA AC007639.1 Promotes the Pathogenesis and Progression of Hepatocellular Carcinoma Through Inhibiting Apoptosis and Stimulating Chemotherapeutic Resistance - Bai, Yun; Ding, Meijuan; Lu, Dan; Li, Yiwen; Yao, Shuai; Wang, Lei; Li, Hui; Cui, Guanghua; Li, Xue; Sun, Xiaoke; Yang, Yu (Frontiers in Oncology, 2021)
Background: Hepatocellular carcinoma (HCC) is known for its poor prognosis. Long noncoding RNAs (lncRNAs) are critical in the pathogenesis of various types of cancers. We tried to explore the role of lncRNA in the development of HCC. Methods: We identified the role of lncRNA AC007639.1 in the pathogenesis of HCC through bioinformatics and biological experiments in HepG2, Hep3B, and SMMC-7721 cells as well as the nude mice xenograft model. Results: We found that lncRNA AC007639.1 was overexpressed in hepatocellular carcinoma. Knocking down of lncRNA AC007639.1 by specific siRNAs or shRNAs promoted cancer cell death. The growth of mouse xenograft tumors created using lncRNA AC007639.1 deficient HepG2 cells was significantly slowed down. Furthermore, the knockdown of lncRNA AC007639.1 in HCC cells led to the increased expression of p53 and decreased expression of angiopoietin-like 4. Conclusion: LncRNA AC007639.1 was involved in the pathogenesis and progression of hepatocellular carcinoma by inhibition of apoptosis and increasing HCC resistance to chemotherapy.